2019
DOI: 10.1371/journal.pntd.0007542
|View full text |Cite
|
Sign up to set email alerts
|

Developing the first national database and map of lymphatic filariasis clinical cases in Bangladesh: Another step closer to the elimination goals

Abstract: Background The Bangladesh Lymphatic Filariasis (LF) Elimination Programme has made significant progress in interrupting transmission through mass drug administration (MDA) and has now focussed its efforts on scaling up managing morbidity and preventing disability (MMDP) activities to deliver the minimum package of care to people affected by LF clinical conditions. This paper highlights the Bangladesh LF Programme’s success in conducting a large-scale cross-sectional survey to determine the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…A change of either ≥10% or ≥2 cm in circumference was considered clinically relevant, and a change of ≥10% was used for Indurometer scores [ 30 , 31 ]. All analyses were performed using Stata 15.1 (StataCorp, College Station, TX, USA) and a p -value of less than 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A change of either ≥10% or ≥2 cm in circumference was considered clinically relevant, and a change of ≥10% was used for Indurometer scores [ 30 , 31 ]. All analyses were performed using Stata 15.1 (StataCorp, College Station, TX, USA) and a p -value of less than 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…These countries were chosen for their differing populations and stage of MMDP activities. Bangladesh is endemic for LF only and the LF MMDP program has been rolled out to all endemic regions at least once [ 30 ]. In Ethiopia, the national MMDP program is not yet scaled at national levels, and podoconiosis and LF are co-endemic in 29 of 70 LF endemic districts [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…adequate oversight from health workers trained in treating LE, local hydrocoelectomy surgery camps). 16 , 17 New approaches have been used to obtain the burden of LF patients including digital methods 18 , 19 and the use of local clinics; in general, it has been found that in many countries an essential route to locating patients is via local health workers. 17 , 20 …”
Section: The Global Lf Patient Care Programmementioning
confidence: 99%
“… 13 , 14 As of 2018, 944 957 lymphoedema patients and 452 891 hydrocele patients were reported by the countries’ programmes. 10 Enlisting the patients in all IUs using robust methodologies 15 , 16 and expansion of the MMDP measures remains a priority for larger countries in the region. This has been well accomplished in Bangladesh, where more than 30 616 lymphoedema patients and 12 824 hydrocele patients were identified and are being provided with the recommended package of care.…”
Section: Mmdpmentioning
confidence: 99%